2016
DOI: 10.2174/1874123101610010018
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Acetophenone in Supercritical Carbon Dioxide

Abstract: The solubility data of acetophenone in supercritical carbon dioxide (scCO2) were measured using a static method at several temperatures (313.15, 323.15, 333.15, and 343.15K) and pressures ranging from10 MPa to 28 MPa. The density based models (Chrastil and Del valle– Aguilera models) and the Peng-Robinson equation of state (PR-EOS) with quadratic and Stryjek-Vera combining rules were employed to correlate the experimental data. Good correlations between the calculated and experimental solubility data were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The literature search based on the TRC/NIST archive (TDE search) and our own search results revealed that there were no reported experimental VLE data available in the literature for a ternary mixture of propane/ n -butane + acetophenone mixture. However, previously VLE properties of acetophenone in pure supercritical CO 2 and for other acetophenone containing binary systems were studied by several authors. However, the good agreement (see above section 3.1) between the present and reference and reported data from the NIST/TRC database confirms the reliability and accuracy of the method and measured data for the ternary mixture of propane/ n -butane + acetophenone, that is, it gives us assurance that the new design of the high-pressure and high-temperature VLE optical cell is operating correctly.…”
Section: Resultssupporting
confidence: 70%
“…The literature search based on the TRC/NIST archive (TDE search) and our own search results revealed that there were no reported experimental VLE data available in the literature for a ternary mixture of propane/ n -butane + acetophenone mixture. However, previously VLE properties of acetophenone in pure supercritical CO 2 and for other acetophenone containing binary systems were studied by several authors. However, the good agreement (see above section 3.1) between the present and reference and reported data from the NIST/TRC database confirms the reliability and accuracy of the method and measured data for the ternary mixture of propane/ n -butane + acetophenone, that is, it gives us assurance that the new design of the high-pressure and high-temperature VLE optical cell is operating correctly.…”
Section: Resultssupporting
confidence: 70%
“…This effect of pressure can be explained by the increment of SCF density. A number of researches have proven that the solubility of a solute increases with the increase in supercritical solvent density. Tan and Liou found that the desorption activation energy was lower at higher pressure and became proof that regeneration of activated carbons using supercritical CO 2 at higher pressures are more favorable . In this regard, the desorption may be more convenient to occur at a higher operating pressure or higher fluid density.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Also, it can be stated that the results of various reported VLE sources for phenol + CO 2 systems are in good agreement with each other. Based on the results of the previous studies of the phase equilibrium properties of the phenol + CO 2 binary system at a temperature of 373.15 K, it can be concluded that this system in the pressure range up to 30 MPa does not exhibit a liquid–vapor critical point. The critical pressure of this system at a temperature of 373.15 K is about 35 MPa.…”
Section: Introductionmentioning
confidence: 96%
“…VLE and LLE prediction models have been developed by Schmelzer et al based on reported data. , In this paper, the authors provided a comparative analysis of VLE measurements reported in refs for phenol + hydrocarbon (butane, n -heptane, n -octane, n -decane, and n -dodecane) systems, as well as to test suitable methods for the prediction of phase equilibria. The literature search has also revealed that there are several studies of the solubility of phenol in supercritical carbon dioxide, n -heptane, n -octane, and water. Most of these studies reported the solubility of phenol in SC CO 2 . In general, the studies were carried out in a fairly wide range of temperatures from 309 to 363 K and pressures between 7 and 35 MPa.…”
Section: Introductionmentioning
confidence: 99%